A graphene/H-BN van der Waals heterostructure enabling superior (>30 dB) electrical tuning in terahertz devices - A. D. Squires; L.-Z. Song; S. Kuriakose; J. Du; T. van der Laan (npj 2D Materials and Applications)
Abstract Effective control of terahertz radiation is vital for next-generation wireless communication and sensing. However, achieving efficient tuning of the polarisation, amplitude, and phase of terahertz radiation remains challenging. Here, a device using graphene and hexagonal-Boron Nitride demonstrates superior electrical tuning at Terahertz frequencies. The heterostructure device achieves over 30 dB tuning across a 0.2–1.4 THz range with a practical bias of 24 V, outperforming an equivalent graphene-only device by 20 dB. A highly tunable metamaterial terahertz polarisation converter operating at 0.245 THz is produced using this structure. Benchmark tuning of beam ellipticity (0.73) and rotation angle (42o) is achieved at just 15 V, exceeding graphene or complex ionic gel-based devices. This confirms that the heterostructure device tuning can be practically applied to complex devices. The concept of the 2D material heterostructure presented here is adaptable to a plethora of tuneable terahertz devices, opening opportunities for next-generation wireless communications and sensing systems.